Domestic and International Experience and Inspiration on the Innovation Training in Medical-Engineering Talents - Sheng HUANG; Tian LI; Zhenyu YANG; Pengbo HE; Yanglin CHEN; Yibao ZHANG (Yixue yu zhexue)
Medical physics is fundamental for modern clinical services and technological progress in diagnostic and therapeutic radiology, such as radiotherapy, nuclear medicine, and medical imaging. Compared with the traditional model of classified cultivation of medical and engineering talents, the development of medical physics in China is constrained by disciplinary barriers and administrative systems, especially the insufficiency of interdisciplinary innovation and standardized clinical training, which leads to problems such as import-dependence of key technologies and a shortage of high-end medical-radiological resources. Learning from the advanced domestic and international experiences such as those from North America, the International Organization for Medical Physics, the International Atomic Energy Agency, Hong Kong and Duke Kunshan University, and providing development advice for policy making in areas such as education and career development, are of great significance for promoting the collaborative cultivation of medical-engineering innovative talents.